SENGKETA ZONA EKONOMI EKSKLUSIF INDONESIA DENGAN VIETNAM DI WILAYAH LAUT NATUNA UTARA - Jessica Johanna Chirsty; Anto Ismu Budianto (Reformasi Hukum Trisakti, 2021)
The dispute regarding the EEZ border area in the North Natuna Sea with Vietnam is one of the disputes that has been going on for a long time and has not been successfully resolved by forming a bilateral agreement. Unilateral claims made by Indonesia and Vietnam cannot be used as a basis for carrying out activities freely in disputed areas that experience overlap. The problems in this thesis are how to determine the EEZ boundary between Indonesia and Vietnam in the North Natuna Sea area based on the 1982 KHL and how are the efforts made by Indonesia in resolving the dispute over the EEZ boundary determination with Vietnam in the North Natuna Sea area. The research method used is normative legal research which uses secondary data and is supported by interview data with the Pushidrosal TNI AL. Data collection techniques were carried out through library research. The conclusion of this study is that the baseline method used by Indonesia is the archipelagic baseline and Vietnam is the straight baseline. Efforts to resolve the dispute by Indonesia and Vietnam are negotiating a bilateral agreement regarding the delimitation of the EEZ area in the North Natuna Sea.